A Study on the Impact of Growth and Development Screening Education on Posyandu Cadres’ Knowledge - Lisbet Manalu; Dinta; Tonika Tohri (Universitas STRADA Indonesia, 2026)
Background: Early detection of child growth and developmental problems is essential to ensure optimal child outcomes and improve human resource quality. Posyandu cadres play a crucial role in community-based screening; however, limited knowledge and technical skills may hinder effective implementation. Purpose: Educational interventions are therefore needed to strengthen cadres’ capacity in growth and developmental screening. Methods: This study employed a pre-experimental one-group pretest–posttest design conducted in the Ciwaruga Health Center working area. A total of 33 Posyandu cadres were selected using total sampling based on predetermined inclusion criteria. The intervention consisted of structured education delivered through lectures, interactive discussions, and hands-on demonstrations covering anthropometric measurements, growth monitoring charts/ KMS (Kartu Menuju Sehat), developmental screening using the KPSP (Kuesioner Pra Skrining Perkembangan), and referral procedures. Cadres’ knowledge was measured before and after the intervention using a validated and reliable questionnaire. Data were analyzed using descriptive statistics and the Wilcoxon signed-rank test. Results: Before the intervention, most cadres demonstrated low to moderate knowledge levels. Following the educational program, a substantial improvement was observed, with the majority of respondents achieving a high level of knowledge. Statistical analysis revealed a significant difference between pretest and posttest knowledge scores (p < 0.001), indicating the effectiveness of the educational intervention. Conclusions: Growth and developmental screening education significantly improves the knowledge of Posyandu cadres. Structured, practice-oriented educational approaches are effective strategies for enhancing cadre capacity and supporting the quality of community-based child health services.